Exploring EFL students’ pronunciation through the application of AI-powered tool Reading Progress: A case study in Vietnam - Pham, Thuan Duc (Jurnal Cakrawala Pendidikan, 2025)
This study employed AI-powered tool Reading Progress in Microsoft Teams as a tool to investigate challenging sounds encountered by Vietnamese students and to examine the effectiveness of the application in learning English pronunciation. Participants in this six-week study were thirty-four first-year students enrolled in English-as-a-foreign-language (EFL) course at a university in northern Vietnam. Semi-structured interviews with the students and AI-generated analysis results in Reading Progress were used as instruments to collect data. The findings indicated that the five most notable challenging sounds analyzed by AI were /ɪ/, /z/, /ə/, /ʃ/, and /t/. The results also showed significant progress among students across various categories of pronunciation, particularly in reading speed and in the reduction of mispronunciations and omissions through pronunciation training in the tool. Students reported increased engagement and confidence, alongside decreased anxiety, when practicing with Reading Progress. The findings contribute to advancing AI integration in language teaching, offering valuable insights for educators and policymakers. While the study highlights the advantages of Reading Progress in EFL education, limitations include the short duration and the specific text constraints. Future research should investigate long-term effects, diverse language learning contexts, and additional AI tools to maximize learning outcomes.